Ceramide induces macrophage migration inhibitory factor -mediated parthanatos in mouse neurons by increasing ROS levels. (25th September 2022) - Fan, Chenghe; Tian, Yu; Zhang, Yilin; Teng, Junfang; Zhao, Xinyu
Graphical abstract: Highlights: Ceramide induced neuron death through parthanatos. Knockdown of MIF expression inhibited ceramide-induced neuron death. Ceramide induced parthanatos by increasing oxidative stress. Abstract: Ceramides, the key component of sphingolipid metabolism and second messengers, have been associated with neurodegenerative diseases progression and pathology, and can induce neuronal apoptosis and necrosis, but the effect of ceramide on parthanatos has not been fully elucidated. In this study, we investigated the ceramide-mediated parthanatos pathway and the role of macrophage inhibitory factor (MIF) in parthanatos. We found that ceramide significantly diminished the viability and induced the death of primary cortical neurons. These effects were not prevented by treatment with the pan-caspase inhibitor Z-VAD-FMK treatment; in contrast, treatment with the poly (ADP ribosyl) polymerase-1 (PARP-1) inhibitor ABT-888 prevented these ceramide-mediated effects. Specifically, ceramide induced PARP-1 overactivation, increased PAR polymer levels, facilitated apoptosis-inducing factor (AIF) and MIF nuclear translocation and induced DNA damage. Knockdown of MIF with an adenovirus carrying a MIF short hairpin RNA (shRNA) inhibited ceramide-induced DNA damage and neuronal death, but nuclear translocation of AIF was unaffected. Furthermore, ceramide increased reactive oxygen species (ROS) levels, and N -acetyl cysteine (NAC) significantly inhibited PAR production and neuronal death. These findings suggested that ceramide induced neuronal parthanatos by increasing ROS levels and that MIF might be downstream of AIF in the ceramide-mediated parthanatos pathway. In conclusion, our results suggest that knocking down MIF expression may be a potential therapeutic strategy for nervous system diseases.